Salinity Effect on Plant Growth Parameters and Fruit Bioactive Compounds of Two Strawberry Cultivars, Coupled with Environmental Conditions Monitoring - Nikoleta-Kleio Denaxa; Aggeliki Nomikou; Nikolaos Malamos; Eleni Liveri; Petros Anargyrou Roussos; Vasileios Papasotiropoulos (Agronomy, 2022)
Salinity stress is one of the most vital abiotic stresses, impairing the productivity of crops in both irrigated and dry areas. A pot experiment was carried out in a greenhouse environment, aiming to examine the relevant tolerances and evaluate the effect of salinity stress on plant growth, fruit physiological, and quality traits of two strawberry cultivars, Camarosa and Rociera. The plants were irrigated with water with electrical conductivity (EC) of 0.4 dS m−1 (control), or with a salt solution with either ECs 2 dS m−1 (moderate salt stress) or 4 dS m−1 (elevated salt stress). Furthermore, several meteorological parameters, as well as soil moisture, were monitored inside the greenhouse. The results showed that salinity induced osmotic stress, water deprivation, and toxic effects, affecting the growth parameters and yield of both cultivars. The elevated salt stress imposed a negative impact on Rociera’s fruits carbohydrates, organic acids, and anthocyanins, while the antioxidant capacity increased. However, Rociera exhibited high total yield/plant and total yield even under elevated salt stress compared to Camarosa. Camarosa plants grown under high salt levels presented low salinity tolerance index, plant water content, and growth parameters. The fruits exhibited low fresh weight but high sweetness index and antioxidant power. An accumulation of soluble sugars under saline conditions, especially sucrose, was also detected in cv. Camarosa fruits when compared to Rociera. Therefore, the two cvs. exhibited a different pattern of response to salinity stress concerning their physiological, biochemical and nutritional characteristics; however, either could be an interesting alternative for cultivation in areas where a slight salinization of the water or soil imposes a limitation on the rather salt-sensitive crops. Agronomic and biochemical evaluation of salinity stress coupled with monitoring of greenhouse microclimatic conditions will lead to a better understanding of the effects on plant growth and quality characteristics, enhancing the productivity of strawberry cultivars, especially under salt-affected environments.